The Red shoes - Powell, Michael; Walbrook, Anton 1896-1967.; Shearer, Moira 1926-2006.; Goring, Marius 1912-1998.; Hallmark Home Entertainment (Los Angeles, California Hallmark Home Entertainment, 1995)
A beautiful ballerina must choose between dance and romance in this dazzling behind-the-curtain peek at the world of ballet. Moira Shearer is radiant as the young ballet star with the world at her feet, caught in a heartbreaking struggle between the gifted composer she longs for and the dance impresario she lives for.
Anton Walbrook, Marius Goring, Moira Shearer, Leonide Massine, Robert Helpman, Albert Basseman, Esmond Knight, Ludmilla Toberin.
VHS format.
In English ; closed captioned
Keywords: Comedy films; Feature films